Perancangan Aplikasi Manajemen Tugas Berbasis Web Menggunakan Algoritma Greedy untuk Meningkatkan Efisiensi Kerja - Muhamad Fudhail; Chairunnisa Ar Lamasitudju (Jurnal Algoritma, 2026)
This study aims to develop a web-based task management application with the application of the Greedy algorithm to automatically determine task priorities based on urgency and deadlines. The system was developed using a prototyping approach and tested in five work divisions with a total of 50 task data used during the testing process. System performance evaluation was conducted through functional testing, algorithm testing using pre-test and post-test schemes, and usability testing using the System Usability Scale (SUS) method. The test results showed that the application of the Greedy algorithm was able to improve the timeliness of task completion, which in the pre-test stage was in the range of 20%–60% and showed an increase in the post-test stage across all divisions. Usability testing involving 10 respondents resulted in a System Usability Scale (SUS) score of 81, which falls into the Excellent category. These results indicate that the system is not only effective in determining task priorities, but also easy to use and well received by users. This study contributes to the application of the Greedy algorithm in web-based task management systems as an efficient digital solution. However, testing was still conducted on a limited number of users, so further development and evaluation on a larger scale is needed to test the system's performance comprehensively.